Counter-Archive as Methodology: Activating Oral Histories of the Contested Canada-US Border - Reynolds, Johanna; Wu, Grace; Young, Julie (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Remembering Refuge: Between Sanctuary and Solidarity is a counter-archive based on oral history interviews with people who crossed the Canada-US border to seek refuge and advocacy groups working at this border in two moments of crisis: the 1980s Central American crisis and the 2017-19 crisis at Roxham Road. This paper foregrounds counter-archiving as a methodology, building from the oral histories to illustrate how borders and bordering practices are navigated and contested and how these lived experiences push back at state-directed logics and narratives of migration. By drawing connections across past and present struggles over mobilities and borders, we offer a critical genealogy of refuge around the Canada-US border. The oral histories collectively and individually contest state-led narratives of migration as a ‘crisis,’ the need for borders to be further securitized, and specifically of the Canadian state’s generous humanitarianism towards a select few. We introduce the methodological choices, contexts, and limitations of the project’s research design, and present two themes that emerged from the oral histories: the contested element of ‘choice’ in migration movements and the important roles played by resistance and refusal in the working out of borders. Finally, we emphasize that relationships between borders are crucial to understanding the histories of asylum around this border, and the political shift activated by the counter-archive of centering borders as lived, experienced, contested or refused.